2006
DOI: 10.1371/journal.pone.0000097
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Strategy Reveals Biological Pathways and Plasma Biomarker Candidates for Potentially Toxic Statin-Induced Changes in Muscle

Abstract: BackgroundAggressive lipid lowering with high doses of statins increases the risk of statin-induced myopathy. However, the cellular mechanisms leading to muscle damage are not known and sensitive biomarkers are needed to identify patients at risk of developing statin-induced serious side effects.MethodologyWe performed bioinformatics analysis of whole genome expression profiling of muscle specimens and UPLC/MS based lipidomics analyses of plasma samples obtained in an earlier randomized trial from patients eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 32 publications
6
149
1
Order By: Relevance
“…S1). In parallel, other studies performed by using combined genomic and lipidomic analysis showed changes in muscle metabolism (dysregulation of calcium binding proteins and phospholipase C pathway, defective mitochondrial metabolism and activation of pro-apoptosis pathway, dysregulation of cell membrane lipids) contributing to muscle toxicity [39]. Our results showed a down-regulation of several muscle proteins and this effect was…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…S1). In parallel, other studies performed by using combined genomic and lipidomic analysis showed changes in muscle metabolism (dysregulation of calcium binding proteins and phospholipase C pathway, defective mitochondrial metabolism and activation of pro-apoptosis pathway, dysregulation of cell membrane lipids) contributing to muscle toxicity [39]. Our results showed a down-regulation of several muscle proteins and this effect was…”
Section: Discussionsupporting
confidence: 85%
“…This latter finding can be a consequence of the inhibition of the specific targets of the two drugs. Otherwise, the prevalent effect of atorvastatin on the oxidative metabolism pathway can be related to the already described statin-mediated mitochondrial involvement [17,19,39]. Yet, since fenofibrate have no effects on calcium released by mitochondria [17], likely slight effect on the oxidative metabolism were observed here.…”
Section: Muscle Cellular Energy Metabolismmentioning
confidence: 48%
See 1 more Smart Citation
“…The compounds were detected by using electrospray ionization in positive ion mode (ESI+). Data was collected at m/z 300-1200 with a scan duration of 0.2 s. Data was processed using MZmine software version 0.60 [27,28] , and metabolites were identified using internal spectral library or with tandem mass spectrometry as previously described [6,29] .…”
Section: Lipidomicsmentioning
confidence: 99%
“…Sphingomyelins and diacylglycerols were calibrated with PC (17:0/17:0) as an internal standard, while all lysophospholipids were normalized using lysoPC (17:0). Characteristics of the analytical method have been described in detail in the supplement of our previous study (26). The applied platform affords broad screening of multiple lipid classes, including triacylglycerols, cholesterol esters, and major phospholipids, from total lipid extracts within a single sample run.…”
mentioning
confidence: 99%